AUDIT OF FINANCIAL ACTIVITIES BASED ON INTERNATIONAL STANDARDS (Conferencea, 2023)
In Uzbekistan, the path of creating national standards based on international experience was chosen. At the same time, the development of auditing standards in Uzbekistan is based on the assumption that each of them should define some part or aspect of the auditing activity, be short and concise, but contain a fairly complete description of the requirements for regulation of the object of standardization.